An analysis of the effectiveness of wordwall teaching-aid platform on online mandarin as foreign language learning: A study on beginner level at Language Institute of Sanata Dharma University, Yogyakarta - Febbryarta, Khrisna (International Journal Labs, 2024)
Online Mandarin language education, still in its nascent stages, faces several challenges. This study aims to examine the effectiveness of the WordWall platform in enhancing the academic performance of beginner Mandarin language learners enrolled in the comprehensive Mandarin online course at the Language Institute of Sanata Dharma University, Yogyakarta. The study employed a one-group pretest-posttest design, measuring student performance before and after exposure to WordWAll platform. The findings indicate that the platform significantly contributes to improving students' academic performance in learning the Mandarin language. Consequently, it can be concluded that the word-based learning platform serves as an engaging and interactive educational tool that effectively improves students' educational performance in Mandarin language learning.